CT Pulmonary Angiogram with Reduced Radiation Exposure at Low Tube Kilovoltage - Abdullahi Hashi, Ahmed (Jurnal Profesi Medika : Jurnal Kedokteran dan Kesehatan, 2020)
This study's primary goal is to assess the image quality and radiation dose of the low-dose 80kV computed tomography pulmonary angiogram (CTPA) protocol compared to the standard 100kV CTPA protocol for the assessment of pulmonary embolism (PE). The study consisted of 100 patients who had clinically suspected pulmonary embolism and required a CTPA. Patients underwent imaging with a 320-row multi-detector Toshiba Aquilion One Genesis Edition in the absence of the proprietary radiation reduction software known as forward projected model-based Iterative Reconstruction Solution (commercial acronym 'FIRST'). Participants were divided into two groups: A and B. Group A was composed of 50 patients who were allocated to standard CT protocol using a 100 kV exposure setting and all other settings set as a standard by the manufacturer. Group B was composed of 50 patients who were allocated to a CTPA with a low-dose 80kV protocol, standard deviation level 8, an effective mAs of 258, reconstruction algorithm-kernel FC 51 within the lung window, and tube current modulation. A considerable decrease in radiation dose was observed with the low-dose CTPA protocol. The mean radiation dose was also decreased by 66% while using the 80kV protocol than when utilising a standard 100kV technique; this was achieved without compromising this study's diagnostic value. Furthermore, the contrast enhancement was considerably more significant, up to 40% higher when using 80kV. The study found that a low tube voltage of 80kV CTPA protocol resulted in a considerable decrease in radiation dose and improved contrast enhancement without sacrificing the examinations' diagnostic utility.